1997
DOI: 10.1038/bjc.1997.82
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cisplatin pretreatment on the accumulation of MIBG by neuroblastoma cells in vitro

Abstract: Summary [1311]meta-iodobenzylguanidine ([1311]MIBG) provides a means of selectively delivering radiation to neuroblastoma cells and is a promising addition to the range of agents used to treat neuroblastoma. As MIBG is now being incorporated into multimodal approaches to therapy, important questions arise about the appropriate scheduling and sequencing of the various agents employed. As the ability of neuroblastoma cells to actively accumulate MIBG is crucial to the success of this therapy, the effect of chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…3 The only available study using this approach was that of Sisson et al 17 Only 1 of 6 patients completed the entire study protocol, making it difficult to draw any conclusion. Other attempts to increase the 131-MIBG uptake were limited to experimental model systems and included norepinephrine transporter gene transfer 18 and increasing expression of the norepinephrine transporter by pretreatment of tumor cells with cisplatin 19 and retinoic acid combined with interferon-␥ and tumor necrosis factor-␣. 20 In summary, our study demonstrated that the low dose 131-…”
Section: Discussionmentioning
confidence: 99%
“…3 The only available study using this approach was that of Sisson et al 17 Only 1 of 6 patients completed the entire study protocol, making it difficult to draw any conclusion. Other attempts to increase the 131-MIBG uptake were limited to experimental model systems and included norepinephrine transporter gene transfer 18 and increasing expression of the norepinephrine transporter by pretreatment of tumor cells with cisplatin 19 and retinoic acid combined with interferon-␥ and tumor necrosis factor-␣. 20 In summary, our study demonstrated that the low dose 131-…”
Section: Discussionmentioning
confidence: 99%
“…However, observations both 'in vitro' and 'in vivo' in xenograft models (Meco et al, 1997;Riccardi, unpublished observations) and in 6 of our patients, showed no evident alteration in MIBG uptake (Table 4). In fact, it is worth noting that NB cells, pre-incubated with cisplatin, concentrate MIBG more efficiently than untreated NB cells (Armour et al, 1997). Our primary concern was haematological and non-haematological toxicity as a result of this new therapeutic regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical mechanistic justifications for such a combination include enhancement of NET expression or activity, for example, by vorinostat (143); synergistic effect on inhibition of radiation-induced DNA repair, for example, by topoisomerase inhibitors (144); and synergistic elicitation of autophagy and apoptosis, for example, by arsenic trioxide (145). Cisplatin pretreatment may also enhance expression of NET and MIBG uptake (146). Coadministration with poly (adenosine diphosphate) ribose polymerase induced increased DNA damage in xenografts (147).…”
Section: Combination Therapy With Net-targeting Agents With Radiosensmentioning
confidence: 99%